Question
upstudy study bank question image url

Given the function \( y=3 x^{2} \). 1) Determine the equation of the inverse of this function. 2) Sketch the graphs of \( y=3 x^{2} \) and its inverse on the same set of axes and show \( t \) line of symmetry. 3) Calculate the coordinates of the points of intersection between \( y=3 x^{2} \) and its inverse.

Ask by Little Hampton. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The inverse of \( y = 3x^{2} \) is \( y = \sqrt{\frac{x}{3}} \) for \( x \geq 0 \). The graphs of \( y = 3x^{2} \) and its inverse intersect at \( (0, 0) \) and \( \left(\frac{1}{3}, \frac{1}{3}\right) \) on the line \( y = x \).

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

Extra Insights

To determine the inverse of the function \( y=3x^2 \), we first solve for \( x \) in terms of \( y \). 1) Start by swapping \( x \) and \( y \): \[ x = 3y^2 \] Now, solve for \( y \): \[ y^2 = \frac{x}{3} \] \[ y = \pm\sqrt{\frac{x}{3}} \] Since the original function \( y = 3x^2 \) is not one-to-one over all reals, we typically restrict the inverse to the positive branch: \[ y = \sqrt{\frac{x}{3}} \] Thus, the inverse function is \( y = \sqrt{\frac{x}{3}} \). 2) For sketching the graphs, you would plot the parabola \( y = 3x^2 \), which opens upwards, and the line \( y = \sqrt{\frac{x}{3}} \). The line of symmetry is the line \( y = x \), which represents the relationship between a function and its inverse. They intersect along this diagonal line, visually illustrating the symmetry of function-inverse pairs. 3) To find the points of intersection between \( y = 3x^2 \) and its inverse \( y = \sqrt{\frac{x}{3}} \), set the two functions equal to each other: \[ 3x^2 = \sqrt{\frac{x}{3}} \] Squaring both sides gives: \[ (3x^2)^2 = \frac{x}{3} \] \[ 9x^4 = \frac{x}{3} \] Multiplying through by 3 to eliminate the fraction yields: \[ 27x^4 = x \] Rearranging it to bring all terms to one side results in: \[ 27x^4 - x = 0 \] Factoring out \( x \) gives: \[ x(27x^3 - 1) = 0 \] Setting each factor to zero, we get \( x = 0 \) or \( 27x^3 - 1 = 0 \). Solving \( 27x^3 - 1 = 0 \) gives \( x^3 = \frac{1}{27} \), so \( x = \frac{1}{3} \). Substituting \( x = 0 \) and \( x = \frac{1}{3} \) back into either original function: - For \( x = 0 \): \( y = 3(0^2) = 0 \) - For \( x = \frac{1}{3} \): \( y = 3\left(\frac{1}{3}\right)^2 = 3 \cdot \frac{1}{9} = \frac{1}{3} \) Thus, the points of intersection are \( (0, 0) \) and \( \left( \frac{1}{3}, \frac{1}{3} \right) \).

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy